Adverse Childhood Experiences, health insurance status, and health care utilization in middle adulthood. (December 2022) - Testa, Alexander; Jackson, Dylan B.; Vaughn, Michael G.; Ganson, Kyle T.; Nagata, Jason M.
Abstract: Rationale: Adverse childhood experiences (ACEs) negatively impact health over the life-course. Yet, compared to the robust literature on the consequences for ACEs for health, substantially fewer studies assess the implications of exposure to ACEs for health insurance status and health care utilization in adulthood. Objective: To assess the association between accumulating ACEs and (1) an individual's health insurance status, and (2) usual source of care, as well as examine the mediating role of adult socioeconomic status. Methods: Data are from the National Longitudinal Study of Adolescent to Adult Health ( N  = 8, 757). Multinomial logistic regression is used to assess the relationship between ACEs and health insurance status and the usual source of care. Results: Net of control and mediating variables, accumulating exposure to ACEs —particularly four or more ACEs— is associated with a higher likelihood of being uninsured and utilizing the emergency room as the usual source of care. Adult socioeconomic status including educational attainment, household income, employment status, and being uninsured—in the case of usual source of care—substantially mediates these associations. Conclusion: ACEs carry negative repercussions for health insurance and patterns of healthcare utilization that spans into adulthood, and this is largely driven by poor adult socioeconomic status. Highlights: Few studies assess the consequences of ACEs for health care in adulthood. ACEs increases the likelihood of being uninsured by middle adulthood. ACEs increase the use of the emergency room as usual source of care. These associations operate partially through adult socioeconomic status.